The LEGO Mindstorms EV3 discovery book : a beginner's guide to building and programming robots - Valk, Laurens (San Francisco, CA No Starch Press, 2014)
LEGO MINDSTORMS has changed the way we think about robotics by making it possible for anyone to build real, working robots. The latest MINDSTORMS set, EV3, is more powerful than ever, and The LEGO MINDSTORMS EV3 Discovery Book is the complete, beginner-friendly guide you need to get started. Begin with the basics as you build and program a simple robot to experiment with motors, sensors, and EV3 programming. Then you'll move on to a series of increasingly sophisticated robots that will show you how to work with advanced programming techniques like data wires, variables, and custom-made programming blocks. You'll also learn essential building techniques like how to use beams, gears, and connector blocks effectively in your own designs. Master the possibilities of the EV3 set as you build and program: The EXPLOR3R, a wheeled vehicle that uses sensors to navigate around a room and follow lines The FORMULA EV3 RACE CAR, a streamlined remote-controlled race car ANTY, a six-legged walking creature that adapts its behavior to its surroundings SK3TCHBOT, a robot that lets you play games on the EV3 screen The SNATCH3R, a robotic arm that can autonomously find, grab, lift, and move the infrared beacon LAVA R3X, a humanoid robot that walks and talks More than 150 building and programming challenges throughout encourage you to think creatively and apply what you've learned to invent your own robots. With The LEGO MINDSTORMS EV3 Discovery Book as your guide, you'll be building your own out-of-this-world creations in no time! Requirements: One LEGO MINDSTORMS EV3 set
Keywords: Robots -- Diseño y construcción; Robots -- Programación; Lego Minstorms toys; Robótica; Libros electrónicos